2017
DOI: 10.1038/srep42451
|View full text |Cite
|
Sign up to set email alerts
|

Boosting laser-ion acceleration with multi-picosecond pulses

Abstract: Using one of the world most powerful laser facility, we demonstrate for the first time that high-contrast multi-picosecond pulses are advantageous for proton acceleration. By extending the pulse duration from 1.5 to 6 ps with fixed laser intensity of 1018 W cm−2, the maximum proton energy is improved more than twice (from 13 to 33 MeV). At the same time, laser-energy conversion efficiency into the MeV protons is enhanced with an order of magnitude, achieving 5% for protons above 6 MeV with the 6 ps pulse durat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
58
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(63 citation statements)
references
References 58 publications
5
58
0
Order By: Relevance
“…Firstly, when the laser pulse duration is extended to more than 1 ps, such as τ=3 ps, we see from the dashed green line in figure 7(d) that the stable CSA in our scheme can even produce high-flux high-energy proton beams with the peaked energy > 100 MeV and the particle number > 10 12 , which have many applications in high-energy-density science, medicine as well as neutron production. This higher ion energy is achieved due to the significantly increase of laser accelerated/heated electron temperature with longer laser pulse duration, which has been found and identified in [55,56]. In other words, even though at the same laser intensity a 0 , with longer pulse duration, the ion acoustic velocity increases so that shock velocity becomes larger and eventually a higher ion energy is obtained, which has also been discussed in theory [27].…”
Section: Robustness Of the Proposed Schemementioning
confidence: 65%
“…Firstly, when the laser pulse duration is extended to more than 1 ps, such as τ=3 ps, we see from the dashed green line in figure 7(d) that the stable CSA in our scheme can even produce high-flux high-energy proton beams with the peaked energy > 100 MeV and the particle number > 10 12 , which have many applications in high-energy-density science, medicine as well as neutron production. This higher ion energy is achieved due to the significantly increase of laser accelerated/heated electron temperature with longer laser pulse duration, which has been found and identified in [55,56]. In other words, even though at the same laser intensity a 0 , with longer pulse duration, the ion acoustic velocity increases so that shock velocity becomes larger and eventually a higher ion energy is obtained, which has also been discussed in theory [27].…”
Section: Robustness Of the Proposed Schemementioning
confidence: 65%
“…Proton spectra from the highest intensity shots at each pulse duration are shown in figure 3. Taking into account that RCF ion spectrometry is less sensitive than other techniques, such as Thomson Parabola spectroscopy used in [28] and [29], these measurements likely underestimate the cutoff proton energy. Batch-to-batch variations in the sensitivity of the film give rise to a 20%-30% absolute error in determining proton number [43].…”
Section: Resultsmentioning
confidence: 99%
“…Simulations suggest that the multipicosecond interaction will heat plasma electrons beyond the ponderomotive potential of the laser [24][25][26][27]. Indeed, recent experimental results have confirmed that these high energy, multipicosecond laser systems accelerate ions to maximum energies beyond those predicted by traditionally cited scaling laws [28][29][30].…”
Section: Introductionmentioning
confidence: 85%
“…In addition, 1D simulations have been performed by considering the planar plasma expansion in quasi one dimension. 16 In the simulations, recirculating hot electrons have been observed on time scales longer than the incident laser pulse duration. The dynamics of the recirculating hot electrons are more likely responsible for the modulations seen on the time-integrated raw traces of C 1þ ions.…”
Section: Introductionmentioning
confidence: 99%